2011
DOI: 10.1002/polb.22188
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐induced particle orientation and rheological properties of suspensions of organoclays in thermoplastic resins

Abstract: FIGURE 6 TEM image of organoclay/PP nanocomposite, / m ¼ 7 wt %.FIGURE 5 X-ray diffraction patterns of (a) Cloisite 15A, (b) master batch of Cloisite 15A/PPMA, and (c) PP nanocomposite, / m ¼ 7 wt %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Natale and et al found the interaction parameter as q = 0.1, experimentally, for carbon nanotube suspensions . Rajabian and et al introduced the interaction parameter as B and calculated to be equal 0.1 for suspensions of nanoclays in thermoplastic resins .…”
Section: Nanofiber Contributionmentioning
confidence: 99%
“…Natale and et al found the interaction parameter as q = 0.1, experimentally, for carbon nanotube suspensions . Rajabian and et al introduced the interaction parameter as B and calculated to be equal 0.1 for suspensions of nanoclays in thermoplastic resins .…”
Section: Nanofiber Contributionmentioning
confidence: 99%
“…[17][18][19] NET laws provide the means to impose restrictions to the model parameters. Up to date, several micro-structured systems, such as liquid crystals, [20][21][22] polymer melts and solutions, [17][18][19][22][23][24] immiscible complex fluids, [17][18][19][25][26][27] polymer nanocomposites, [28][29][30][31][32][33] drilling fluids, 34 blood, 35 ionomers, 36 and micellar systems, 37 have been addressed through NET, a fact that attests to its usefulness and applicability. To the best of our knowledge, only the model proposed by Beris et al 38 for concentrated star polymer suspensions, a system exhibiting a yield stress, was derived via the use of NET principles.…”
Section: Introductionmentioning
confidence: 99%